Low-temperature ZrO2 thin films obtained by polymeric route for electronic applications - Boratto, Miguel H. [UNESP]; Lima, João V. M. [UNESP]; Scalvi, Luis V. A. [UNESP]; Graeff, Carlos F. O. [UNESP] (Springer Nature, 2020)
In this work, zirconium oxide (ZrO2) films obtained by the polymer-assisted chemical solution method were evaluated. Thin films are obtained using dip-coating with dipping rates from 1 to 100 mm/min, and annealing temperatures from 150 to 450 °C. The films present amorphous structure even with annealing at 450 °C, bandgap of 5.4 eV and a non-porous surface. The zirconia films were electrically characterized applied to a metal–insulator–metal capacitor (MIM-c) configuration. The dielectric layer presents high capacitance and impedance, highly dependent on the dipping rates and annealing temperature. The outcomes from the MIM-c investigated demonstrate that this low-temperature zirconia film may be an alternative for application in flexible electronic devices as insulating layer. More interesting results like higher capacitance and higher operation frequencies are obtained for zirconia layers obtained at 350 °C due to better dipole formation in the film enhanced by the thinner films and a better elimination of polymeric ligands in the film.